2000
DOI: 10.1054/jhsb.1999.0277
|View full text |Cite
|
Sign up to set email alerts
|

De Quervain’s Disease

Abstract: The basic anatomy of the first extensor compartment is presented with a review of the pathology of de Quervain's stenosing tenovaginitis. The results in 100 medicolegal cases of de Quervain's disease are analysed and reasons are sought for the poor results. A review of the known factors associated with the causation of de Quervain's disease is presented with recommendations about the management of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 10 publications
0
19
1
Order By: Relevance
“…De Quervain's disease was first recognized in 1895 as a stenosing tenosynovitis of the abductor pollicis longus (APL) and the extensor pollicis brevis (EPB) within the first extensor compartment of the wrist, formed by the radius and dorsal carpal ligaments 1 , 2 , 3) rather than inflammation. 4) As pathology specimens demonstrate collagen disorientation and mucoid change, 5 , 6) it may be more appropriate to regard de Quervain's disease as tendinosis rather than tendinitis.…”
mentioning
confidence: 99%
“…De Quervain's disease was first recognized in 1895 as a stenosing tenosynovitis of the abductor pollicis longus (APL) and the extensor pollicis brevis (EPB) within the first extensor compartment of the wrist, formed by the radius and dorsal carpal ligaments 1 , 2 , 3) rather than inflammation. 4) As pathology specimens demonstrate collagen disorientation and mucoid change, 5 , 6) it may be more appropriate to regard de Quervain's disease as tendinosis rather than tendinitis.…”
mentioning
confidence: 99%
“…Failure to release such a compartment surgically is a recognized cause of persisting symptoms following surgical release. 5 Failure to alleviate symptoms with a steroid injection may be due to an extra compartment, which may not have been penetrated and may require a repeat injection. 3 Mr Ndiyamba is correct that all treating personnel and surgeons should be aware of anatomical variations and their implications not only in musicians and should document when such variations are shown to exist.…”
Section: Authors' Replymentioning
confidence: 99%
“…4 Likewise an accurate injection into both the EPB and APL tendon sheaths by the two-point injection method may be more effective for de Quervain's disease rather than the techniques that do not take the anatomical variation into consideration. 5 I would be interested in knowing if they came across any variants and if not, I suggest that future research documents such findings for teaching a very important concept in anatomy that may affect function, as in musicians' hands. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This shift had already in fact happened, as in a case heard in 1992 (pre-dating the 1992 regulations), which involved De Quervain's disease and keyboard usage. Sound medical evidence had demonstrated that Mrs Mulligan's thumb could not have been stressed or used excessively in normal keyboard usage and therefore typing could not have caused, in the medical sense, De Quervain's disease (Kay, 2000). However, ample evidence was produced of unsafe working practices by the bank which the bank could not defend.…”
Section: New Health and Safety Regulationsmentioning
confidence: 99%